Analysis of Organic and Conventional Lowland Rice (Oryza Sativa L) Cultivation Systems in Supporting Environmentally Friendly Agriculture in Beringin District, Deli Serdang Regency - Zulfansyah, Ichfan; Rahmawati, Nini; Delvian (TALENTA Publisher, Universitas Sumatera Utara, 2021)
The application of organic agriculture in lowland rice farming is one of the interesting topics in an effort to reduce environmental pollution caused by the use of chemical fertilizers and pesticides. This study aimed to determine the level of production and analyze the environmental impact of the soil from the application of organic and conventional agriculture in the Banyan District, Deli Serdang Regency. The results showed that 1) There was a significant difference between the production of harvested dry grain (GKP) of organic paddy and the production of harvested dry grain (GKP) of conventional lowland rice. 2) The level of soil fertility in organic and conventional lowland rice farming has low criteria